2015
DOI: 10.1021/acs.iecr.5b00362
|View full text |Cite
|
Sign up to set email alerts
|

Refuse-Derived Fuel and Integrated Calcium Hydroxide Sorbent for Coal Combustion Desulfurization

Abstract: Pelletized refuse-derived fuel (RDF; 65 wt % nonrecyclable fibers/plastics) and integrated calcium hydroxide sorbent (35 wt %), referred to as a ReEngineered Feedstock (ReEF), were evaluated as a renewable fuel and an in situ sulfur sorbent within pulverized coal combustion. Characterization of ReEF with scanning electron microscopy–energy-dispersive X-ray spectroscopy indicated random distribution of calcium hydroxide sorbents on fiber/plastic particles. The sulfation kinetics of ReEF combustion were evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Calcium hydroxide find applications in dentistry [1], bone treatment [2], conservation of cultural heritage [3,4]. It is also being utilized for desulfurization [5] and CO2 capture [6]. Alcohol dispersion of this materials is helpful to conserve stone [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Calcium hydroxide find applications in dentistry [1], bone treatment [2], conservation of cultural heritage [3,4]. It is also being utilized for desulfurization [5] and CO2 capture [6]. Alcohol dispersion of this materials is helpful to conserve stone [7].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, this technique also give information about self-induced strain, crystallite size, and microstructural information of synthesized materials [19][20][21]. Not only, structural behavior but morphological investigation is essential for synthesized material since the shape and size play important roles in determining their efficiency for particular application [1][2][3][4][5][6]. Scanning electron microscopy has been identified to investigate morphological behavior of nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Ca-based sorbents are the well-known and commonly used sorbents for SO 2 removal from combustion gases because of their wide availability, low price, and high efficiency. Guan carried out combustion experiments of coal with three kinds of calcium-based sulfur fixing agents (CaO, Ca­(OH) 2 , and CaCO 3 ) and found that Ca­(OH) 2 had a better effect on sulfur fixation and CaCO 3 promoted the release of SO 2 at low temperatures. The CaCO 3 /CaO solid sorbent particle size had a significant effect on SO 2 capture, and mixed solid sorbent had higher capture efficiency than the conventional pure solid sorbent .…”
Section: Introductionmentioning
confidence: 99%
“…To reduce SO 2 emission, inhibiting SO 2 emissions during coal combustion processes has been the focus to protect the atmospheric environment . Coal sulfur-fixing agents, such as CaCO 3 , CaO, Ca­(OH) 2 , MgCO 3 , MgO, Na 2 CO 3 , and NaOH, are crucial for limiting sulfur dioxide emissions during coal combustion. , Sulfur-fixing agents include calcium-based sorbents (CaCO 3 , CaO, and Ca­(OH) 2 ) and alkaline residues (carbide slag, waste paper, boron mud, natural minerals, and other industrial waste salt and limestone). The most widely used and cheap sulfur-fixing agents are calcium-based sorbents (CaCO 3 , CaO, and Ca­(OH) 2 ). Because calcium-based sulfur-fixing products (CaSO 4 ) decompose easily at high temperatures, many scholars have studied the methods for reducing CaSO 4 decomposition at high temperatures and found that the addition of alkali metal oxides or alkaline have efficient effects. For example, Sm-based and Mn-/SBA-15 sulfur-fixing agents can effectively inhibit SO 2 emissions from coal combustion. , In addition, based on the properties of calcium-based sulfur-fixing agents, SiO 2 , CuO, ZnO, Fe 2 O 3 , and other substances have shown certain synergistic effects on sulfur-fixing processes. , Therefore, the studies on the compounds in sulfur-fixing agents have received significant interest in recent years; however, synthetic or natural sulfur-fixing agents have high costs.…”
Section: Introductionmentioning
confidence: 99%
“…1 Coal sulfur-fixing agents, such as CaCO 3 , CaO, Ca(OH) 2 , MgCO 3 , MgO, Na 2 CO 3 , and NaOH, are crucial for limiting sulfur dioxide emissions during coal combustion. 2,3 Sulfur-fixing agents include calcium-based sorbents (CaCO 3 , CaO, and Ca(OH) 2 ) and alkaline residues (carbide slag, waste paper, boron mud, natural minerals, and other industrial waste salt and limestone). 7−9 The most widely used and cheap sulfurfixing agents are calcium-based sorbents (CaCO 3 , CaO, and Ca(OH) 2 ).…”
Section: Introductionmentioning
confidence: 99%